2015
DOI: 10.1002/2014jd022766
|View full text |Cite
|
Sign up to set email alerts
|

Observing and modeling the influence of layering on bubble trapping in polar firn

Abstract: Interpretation of ice core trace gas records depends on an accurate understanding of the processes that smooth the atmospheric signal in the firn. Much work has been done to understand the processes affecting air transport in the open pores of the firn, but a paucity of data from air trapped in bubbles in the firn-ice transition region has limited the ability to constrain the effect of bubble closure processes. Here we present high-resolution measurements of firn density, methane concentrations, nitrogen isoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 61 publications
(156 reference statements)
1
97
1
Order By: Relevance
“…5). The weaker-than-expected smoothing during DO-17 at Vostok could be due to the presence of a strong layering preventing air renewal and mixing, as suggested in Mitchell et al (2015).…”
Section: Understanding the Smoothing Of Ice Core Signals Under Low-acmentioning
confidence: 99%
See 4 more Smart Citations
“…5). The weaker-than-expected smoothing during DO-17 at Vostok could be due to the presence of a strong layering preventing air renewal and mixing, as suggested in Mitchell et al (2015).…”
Section: Understanding the Smoothing Of Ice Core Signals Under Low-acmentioning
confidence: 99%
“…For example, pore closure anomalies have been associated with tortuosity anomalies, with more tortuous layers closing earlier (Gregory et al, 2014), or to density anomalies, with denser layers closing earlier Mitchell et al, 2015;Rhodes et al, 2016). In this section we used the latter hypothesis supported by observed relationships between local density and closed porosity (e.g., Stauffer et al, 1985;Mitchell et al, 2015) to test whether density-driven anomalies could result in artifacts as observed in the Vostok methane record.…”
Section: Simple Model Of Layered Trappingmentioning
confidence: 99%
See 3 more Smart Citations